Employment protection under fire: Labour market deregulation and employment in the European Union. (November 2014) - Heyes, Jason; Lewis, Paul
Employment protections are currently being targeted by European policy makers seeking solutions to persistently high levels of unemployment and weak economic growth. This article argues that labour market deregulation is unlikely to usher in a period of renewed growth in good quality jobs. The findings point to the important role of employment protections in stemming job losses in the initial stages of the economic crisis that began in 2008, although protections have not prevented subsequent heavy job losses in the most distressed economies. The study also finds that involuntary participation in non-standard employment has increased since the crisis and shows that this has resulted in an increased risk of in-work poverty.